2021
DOI: 10.1186/s12884-020-03485-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends in and determinants of visiting private health facilities for maternal and child health care in Nepal: comparison of three Nepal demographic health surveys, 2006, 2011, and 2016

Abstract: Background Maternal and child health care services are available in both public and private facilities in Nepal. Studies have not yet looked at trends in maternal and child health service use over time in Nepal. This paper assesses trends in and determinants of visiting private health facilities for maternal and child health needs using nationally representative data from the last three successive Nepal Demographic Health Surveys (NDHS). Methods Da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(40 citation statements)
references
References 38 publications
0
39
1
Order By: Relevance
“…This might be related to the increased nutritional needs of younger women and additional requirements imposed due to prior pregnancy and recent lactation [ 35 ]. On top of the physiological vulnerability, inadequate use of maternal health services like ANC and skilled birth attendance among young mothers may contribute to the increment of the prevalence of undernutrition [ 36 ]. Another study conducted in Jimma Zone, Southwest Ethiopia, showed that undernutrition was not associated with the age of the mothers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to the increased nutritional needs of younger women and additional requirements imposed due to prior pregnancy and recent lactation [ 35 ]. On top of the physiological vulnerability, inadequate use of maternal health services like ANC and skilled birth attendance among young mothers may contribute to the increment of the prevalence of undernutrition [ 36 ]. Another study conducted in Jimma Zone, Southwest Ethiopia, showed that undernutrition was not associated with the age of the mothers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors associated with ethnicity minorities and socioeconomic status may increase the disease’s burden and should therefore not be overseen [ 29 , 30 ]. Geographical differences might further affect the outcomes of COVID-19, due to differences in therapeutic management and adherence to preventive measures [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Namely, visitor restrictions, increased use of technology, and decreased face-to-face interactions have changed our communication landscape, while providers and families alike are facing catastrophic times of job insecurity, limited interaction with distant family members, serious illness, and death. Women in the perinatal period are uniquely impacted by the current pandemic, with pregnancy and childbirth occurring in difficult conditions [ 51 , 52 ]. Pregnant women are now often alone for prenatal sonograms and visits with specialty physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women are now often alone for prenatal sonograms and visits with specialty physicians. When faced with a critical fetal diagnosis, this lack of support along with fears over pregnancy loss and contracting serious illness has adversely affected maternal mental health [ 52 ]. These unique challenges highlight a broad need for early PC consultation, although their full impact remains to be studied.…”
Section: Discussionmentioning
confidence: 99%